Computer security self-efficacy effect: an extension of Technology-to-Performance Chain Model - Al-Shawabkeh, Mahmoud; Mohd Saudi, Madihah; Mohd Alwi, Najwa Hayaati (2012)
given a paucity of research and apparent lack of coherence in information system research, it seems that there is no consensus in the information system field as to how security fits into the information system acceptance, usage, success, utilization, and/or performance impact (effectiveness, efficiency, and satisfaction). This paper is part of an ongoing research project designed to extend the Technology-to-Performance Chain (TPC) model by including the Computer Security Self-Efficacy (CSSE) construct, a strategy of model extension suggested by several researchers. This project aims to examine the research conducted in the last decade in information system journals regarding security issues then based on social cognitive theory, to propose a construct to measure individuals’ computer security self-efficacy. Based on the Technology-to-Performance Chain (TPC) model, this study design expected to models and tests relationship among computer security self-efficacy and secures online banking system performance impact. The study will try to answer the question “to what extent has the computer security self-efficacy affected user’s perception of secure online banking system effectiveness“. After this research finished, the researcher assume that this study findings will provides an initial step towards understanding of the applicability of social cognitive theory in information system security domain and helps information security professionals design information systems considering the effect of computer security self-efficacy on secure information system.